Jugoslavenska Žena/Yugoslav Woman – The Forum Of Modern Woman Writer (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The affirmation and promotion of female authorship is one of the basic aspects of emancipatory discourse in the magazine Jugoslavenska žena/Yugoslav woman (1917-1920). The emphasis on the importance and necessity of female self expression and self representation is one of the commonplaces in the program texts. The paradigm of female authorship was exhibited in essays and studies on women writers and in the original literary work. Women’s literature is not subordinated to enlightened and pragmatic objectives of the magazine, but reflects the sensitivity, aesthetic and creative abilities, expressive possibilities and thematic interests of its authors. Poetic pluralism (the realist, symbolist, romantic, expressionist tendencies) is an innovation that brings the magazine in relation to women’s periodicals, pointing out that the concept of modern woman writer includes the construction of personal and independent style and poetic characteristics. This model of woman writer represents another step in the development of female authorship in the context of feministic discursive space and network of communications.
Keywords: Yugoslav woman; Zofka Kveder; women’s periodicals; female authorship; modern woman